2018
DOI: 10.3389/fnagi.2018.00167
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Functional Connectivity of Anterior Cingulate Cortex in Patients With Primary Insomnia: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Background: Recently, there have been many reports about abnormalities regarding structural and functional brain connectivity of the patients with primary insomnia. However, the alterations in functional interaction between the left and right cerebral hemispheres have not been well understood. The resting-state fMRI approach, which reveals spontaneous neural fluctuations in blood-oxygen-level-dependent signals, offers a method to quantify functional interactions between the hemispheres directly.Methods: We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…The relationship between slow-wave and fast-wave activity is known as the cross-talk between the subcortical and cortical brain regions [46,47]. Increased slow-fast wave coupling is considered to reflect increased attentional control [48] and cortisol levels [49], and many studies using fMRI also found that chronic insomnia patients showed abnormal brain connectivity [50,51]. In this regard, this result may suggest that insomnia patients have higher cognitive activity and greater load on the brain by accepting excessive information from external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between slow-wave and fast-wave activity is known as the cross-talk between the subcortical and cortical brain regions [46,47]. Increased slow-fast wave coupling is considered to reflect increased attentional control [48] and cortisol levels [49], and many studies using fMRI also found that chronic insomnia patients showed abnormal brain connectivity [50,51]. In this regard, this result may suggest that insomnia patients have higher cognitive activity and greater load on the brain by accepting excessive information from external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that communication between the left and right hemispheres of the human brain is crucial for cognition and emotion processing (14). The VMHC has also been applied to study Parkinson's disease, schizophrenia, and insomnia (15). Additionally, previous VMHC analyses of stroke have shown that altered VMHC is associated with motor function assessment and illness duration (16).…”
Section: Introductionmentioning
confidence: 99%
“…Baseline characteristics have previously been described in detail ( 41 ). A total of 26 PI patients and 28 healthy controls were enrolled.…”
Section: Resultsmentioning
confidence: 99%